Potential therapeutic effects of Ebixa, Ginkgo biloba, and selenium in a cadmium chloride-induced Alzheimer’s disease manifestations in rats - Alrikabi, Afaf; Allahyani, Wasayf; Shaghath, Amjad; Alrashdi, Jawaher; Almoqhem, Reem; Alasmari, Fawaz; Al-Qerem, Walid; Albasher, Gadah (Frontiers in Neuroscience, 2025)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder characterized by cognitive decline and neuronal damage. Cadmium exposure has been implicated in AD pathogenesis. This study aimed to investigate the potential therapeutic effects of Ebixa (memantine), Ginkgo biloba, and selenium in a cadmium-induced rat model of AD. Adult male Wistar rats were divided into six groups: control, control + Ginkgo-treated, cadmium chloride (CdCl2), CdCl2 + Ebixa-treated, CdCl2 + Ginkgo, and CdCl2 + Ginkgo + Selenium. Behavioral tests, including the Morris water maze and passive avoidance learning, were conducted. Additionally, biochemical analysis of acetylcholine (Ach), choline acetyltransferase (AchT), and acetylcholinesterase (AChE) levels in brain homogenates was performed. Histological sections of the cerebral cortex, cerebellum, and medulla were examined. Apoptotic assessment was conducted using the TUNEL assay. CdCl2 exposure resulted in cognitive deficits, reduced Ach levels, and neuronal damage, mirroring AD-like characteristics. Ebixa treatment improved spatial memory behavior as well as Ach, AchT and AChE levels in the brain. Ginkgo biloba and selenium co-administration increased the number of crossings in the Morris water maze test, suggesting memory preservation. Additionally, Ginkgo biloba exhibited potential cholinergic system protective effects. Histological analysis revealed neuroprotection in the cerebral cortex, cerebellum, and medulla. TUNEL assays demonstrated anti-apoptotic effects of both Ebixa and the combination of Ginkgo and selenium. Ebixa, Ginkgo biloba, and selenium showed promise in mitigating cognitive deficits and preserving neuronal structures in a CdCl2-induced AD manifestation in rats. These findings provide insights into potential therapeutic strategies for AD and warrant further investigation.